The American Alligator: An Indicator Species for Everglades Restoration - Rebecca G. Harvey; Frank J. Mazzotti; Laura A. Brandt (EDIS)
Scientists working on Everglades restoration cannot monitor everything in the ecosystem to determine the effectiveness of their efforts, so they use “ecological indicators” such as the American alligator. Learn how this works in this 3-page fact sheet written by Rebecca G. Harvey, Frank J. Mazzotti, and Laura A. Brandt, and published by the UF Department of Wildlife Ecology and Conservation, October 2011. Reviewed October 2014.